Exploration of leads from bis-indole based triazine derivatives targeting human aldose reductase in diabetic type 2: In-silico approaches - Roney, Miah; Issahaku, Abdul Rashid; Mohammed Nazim, Uddin; Wilhelm, Anke; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer Science and Business Media Deutschland GmbH, 2025)
Diabetes mellitus (DM) poses a major global healthcare challenge, highlighting the need for new treatments beyond current options. Currently available drugs have side effects including weight gain, nausea, vomiting, diarrhea, insulin resistance etc. Therefore, given the benefits of indole derivatives in diabetes and the lack of computational studies on bis-indole-based triazine derivatives with aldose reductase (AR), this study employs in-silico analysis to explore their potential as type-2 diabetes treatments. Based on the Differential Expression analysis, the human aldose reductase (HAR) encoding gene AKR1B1 showed overexpression in GSE30122 diabetes patients (Log2FC = 0.62, P < 0.01). Moreover, the compounds 2-((5,6-di(1H-indol-3-yl)-1,2,4-triazin-3-yl)thio)-1-(3-hydroxy-5-methylphenyl)ethan-1-one (4) and 2-((5,6-di(1H-indol-3-yl)-1,2,4-triazin-3-yl)thio)-1-(4-nitrophenyl)ethan-1-one (8) were identified as leading candidates, showing binding energies of − 62.12, − 81.73 kcal/mol and − 57.19, − 85.97 kcal/mol, respectively. Docking, MM/GBSA screening, molecular dynamics (MD) simulations, PCA, and post-MM/GBSA analysis confirmed their stability and favorable binding compared to the apo protein and control. Further in-vitro, in-vivo, and clinical studies are required to validate their therapeutic potential.